215k views
24 votes
1.) Solve.

9 + 3x = 5(−x + 5) − 56
x =

2.) this answer is the picture on the bottom it would say 8 so put the equation. for me


3.)Solve.
−5(2x − 21) = 2(x − 4) − 31
x =


4.)Solve the equation.
3(x + 5) = 2(3x + 18)
x =

1.) Solve. 9 + 3x = 5(−x + 5) − 56 x = 2.) this answer is the picture on the bottom-example-1
User Chiducaf
by
5.2k points

1 Answer

6 votes

Answer:

For the first one, I got -11.25= x.

Explanation:

9+3x=-5(-x+5)-56

9+3x=-5x-81

9+8x=-81

8x=-90

-90/8= -11.25

User DragoJokera
by
5.1k points